Few-layered Ti3C2Tx MXenes coupled with Fe2O3 nanorod arrays grown on carbon cloth as anodes for flexible asymmetric supercapacitors. Issue 39 (30th September 2019) - Li, Fei; Liu, Yi-Lin; Wang, Gui-Gen; Zhang, Hua-Yu; Zhang, Bin; Li, Gui-Zhong; Wu, Zhi-Peng; Dang, Le-Yang; Han, Jie-Cai
Abstract : Few-layered Ti3 C2 T x MXene wrapped Fe2 O3 nanorod arrays grown on carbon cloth, is a promising anode for high-performance flexible asymmetric supercapacitor. Abstract : The design of flexible electrodes with high areal capacitance is the key for the application of flexible asymmetric supercapacitors (ASCs) in portable and wearable electronics. In this study, Ti3 C2 T x MXene coupled with the Fe2 O3 /CC flexible negative electrode, with good conductivity, high areal capacitance, and excellent flexibility, was fabricated by a simple dipping method, in which the as-grown Fe2 O3 nanorod arrays on carbon cloth were dipped into the few-layered MXene nanosheet solution repeatedly to make the Fe2 O3 /CC fibers wrapped with MXene completely. The MXene@Fe2 O3 /CC electrode presents a remarkable areal capacitance of up to 725 mF cm −2 at a current density of 1 mA cm −2 which was contributed by both MXene and Fe2 O3 nanorods. As to the MXene layer, it not only offers capacitance for the flexible electrode, but also provides fast and efficient ion/electron transport pathways for Fe2 O3 to effectively improve electronic conductivity. Besides, the as-constructed ASC devices consisting of MXene@Fe2 O3 and MnO2 electrodes achieve a high energy density of 1.61 mW h cm −3 at a power density of 22.55 mW cm −3 along with good stability. The work provides a simple effective strategy to load active materials on carbon fibres and to construct hierarchical coating-structured electrodes for high-performance flexible ASC application.